The use of sirolimus in the treatment of giant cystic lymphangioma: Four case reports and update of medical therapy. Issue 51 (December 2017) - Amodeo, Ilaria; Colnaghi, Mariarosa; Raffaeli, Genny; Cavallaro, Giacomo; Ciralli, Fabrizio; Gangi, Silvana; Leva, Ernesto; Pignataro, Lorenzo; Borzani, Irene; Pugni, Lorenza; Mosca, Fabio
Abstract: Rationale: Lymphatic malformations (LMs) are rare and benign anomalies resulting from the defective embryological development of the primordial lymphatic structures. Due to their permeative growth throughout all tissue layers, treatment is often challenging. Small asymptomatic lesions can be conservatively managed, while symptomatic lesions require active management. Surgery has been historically considered the treatment of choice, but today less invasive therapeutic options are preferred (sclerotherapy, laser therapy, oral medications). However, there are not uniform therapeutic protocols. Sirolimus is an oral medication that has been reported to be effective in the recent literature. Here we present the case of 4 newborns with giant multicystic lymphangioma treated with oral sirolimus after surgical resection had failed. Patient concerns: At birth the LMs were clinically appreciated as giant masses involving different organs and structures. Diagnoses: All patients had a prenatal diagnosis of giant multicystic lymphangioma confirmed at histological and cytological analysis. Interventions: Patients were treated with oral sirolimus after unsuccessful surgical resection. Outcomes: In all patients, sirolimus determined an overall reduction of the mass and a global involution from the macro- to the microcystic composition. Sirolimus was safe and poor disadvantages had been observed. The main and isolated adverse effect at laboratory analysis was progressive dyslipidemia, with increasing levels of total cholesterol and triglycerides. Lessons: To date, our experience with sirolimus in the management of LMs is favorable. We recommend the use of sirolimus after unsuccessful surgical excision have been tried or when the surgical approach is not feasible. A multidisciplinary follow-up is needed to monitor disease evolution.